A nuclease- and bisulfite-based strategy captures strand-specific R-loops genome-wide - Phillip Wulfridge; Kavitha Sarma (eLife, 2021)
R-loops are three-stranded nucleic acid structures with essential roles in many nuclear processes. However, their unchecked accumulation is associated with genome instability and is observed in neurodevelopmental diseases and cancers. Genome-wide profiling of R-loops in normal and diseased cells can help identify locations of pathogenic R-loops and advance efforts to attenuate them. We present an antibody-independent R-loop detection strategy, BisMapR, that combines nuclease-based R-loop isolation with non-denaturing bisulfite chemistry to produce genome-wide profiles that retain strand information. BisMapR achieves greater resolution and is faster than existing strand-specific R-loop profiling strategies. In mouse embryonic stem cells, we apply BisMapR to find that gene promoters form R-loops in both directions and uncover a subset of active enhancers that, despite being bidirectionally transcribed, form R-loops exclusively on one strand. BisMapR reveals a previously unnoticed feature of active enhancers and provides a tool to systematically examine their mechanisms in gene expression.